Immediate and short-term effects of gait retraining on the knee joint moments and symptoms in patients with early tibiofemoral joint osteoarthritis: a randomized controlled trial. Issue 11 (November 2018) - Cheung, R.T.H.; Ho, K.K.W.; Au, I.P.H.; An, W.W.; Zhang, J.H.W.; Chan, Z.Y.S.; Deluzio, K.; Rainbow, M.J.
Summary: Objective: To evaluate the effectiveness of a knee adduction moment (KAM) gait retraining in patients with early knee osteoarthritis up to 6 months post-training. Method: We conducted a single blinded randomized controlled trial on a total of 23 patients with early knee osteoarthritis who were randomly allocated to the gait retraining group and walking exercise group. Twenty of them completed the corresponding training and the 6-month evaluation. We measured KAM, knee flexion moment (KFM) and western ontario and McMaster universities osteoarthritis index (WOMAC) osteoarthritis index before, immediate after, and 6 months after training. A repeated measures analysis of covariance (ANCOVA) was used to compare KAM, KFM and WOMAC osteoarthritis index scores across the three time points i.e., pre-training, post-training, and 6-month follow-up with gender, knee osteoarthritis severity, and pre-training KAM, KFM and WOMAC scores set as covariates. Post-hoc analyses were conducted when indicated. Results: Significant time × group interactions were found for both KAM and WOMAC osteoarthritis index scores ( P < 0.002). No interaction was found for KFM ( P = 0.123). KAM after gait retraining was significantly lower than the pre-training value ( P < 0.001) and such effect was maintained at 6-month follow-up ( P = 0.01). There was no significant difference in the KAM across time in the walking exercise group ( P > 0.208). WOMAC osteoarthritis index score after training and score at the 6-month follow-up were significantly improved in the gait retraining group ( P = 0.001), while the WOMAC osteoarthritis index score remained similar. Conclusions: Gait retraining is an effective intervention to reduce KAM during walking and to improve the symptoms of patients with early knee osteoarthritis in short term.